New Psychoactive Substances: Health and Legal Challenges - Inês C. Santos; Daniela Maia; Ricardo Jorge Dinis-Oliveira; Daniel José Barbosa (MDPI AG, 2024)
Drug abuse represents a significant public health problem with a growing tendency. As a way of circumventing the strict national and international control of psychoactive substances by regulatory agencies, there is a market release of new substances with psychoactive activity, called New Psychoactive Substances (NPSs). This group of substances encompasses a diverse range of synthetic compounds designed to mimic the effects of traditional illicit substances. As NPSs show stronger psychoactive effects than classical drugs, they pose unique challenges to public health and regulatory frameworks. Additionally, some substances are considered NPSs in some countries but not in others. Therefore, based on a given legal definition, manufacturers can create an NPS that does not fall under that definition and thus is not prohibited. This review critically explores the multifaceted dimensions of the criminal and legal contexts associated with NPSs. It examines the trends of abuse, the intricate network of criminal and legal aspects surrounding these substances, and the crucial warning signs that indicate their emergence, highlighting the health risks posed by these substances. In conclusion, this manuscript addresses the intricate interplay between the pharmacology, risks, and regulatory responses. These multifaceted challenges associated with NPSs will likely provide valuable insights for future research.